1996
DOI: 10.1128/mcb.16.7.3381
|View full text |Cite
|
Sign up to set email alerts
|

The DNA-Binding and Enhancer-Blocking Domains of the Drosophila suppressor of Hairy-wing Protein

Abstract: Mutations in the suppressor of Hairy-wing [su(Hw)] gene of Drosophila melanogaster can cause female sterility and suppress mutations that are insertions of the gypsy retrotransposon. Gypsy binds the protein (SUHW) encoded by su(Hw), and SUHW prevents enhancers promoter-distal to gypsy from activating gene transcription. SUHW contains 12 zinc fingers flanked by acidic N-and C-terminal domains. We examined the roles of each of the 12 zinc fingers in binding gypsy DNA and classified them into four groups: essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 64 publications
4
76
0
3
Order By: Relevance
“…2B) probably corresponds to a complex of the 125 bp DNA fragment with one Su(Hw) protein. The inability of the Su(Hw) protein to simultaneously bind two closely spaced sites was previously described by Kim et al (Kim et al, 1996) who suggested that the Su(Hw) protein interferes with binding to neighboring sites. To show that both putative binding sites in the 125 bp fragment can interact with Su(Hw), we subcloned smaller fragments that contain only the first or the second Su(Hw) binding site ( Fig.…”
Section: The Yellow-ac Intergenic Region Contains a Functional Su(hw)mentioning
confidence: 99%
See 1 more Smart Citation
“…2B) probably corresponds to a complex of the 125 bp DNA fragment with one Su(Hw) protein. The inability of the Su(Hw) protein to simultaneously bind two closely spaced sites was previously described by Kim et al (Kim et al, 1996) who suggested that the Su(Hw) protein interferes with binding to neighboring sites. To show that both putative binding sites in the 125 bp fragment can interact with Su(Hw), we subcloned smaller fragments that contain only the first or the second Su(Hw) binding site ( Fig.…”
Section: The Yellow-ac Intergenic Region Contains a Functional Su(hw)mentioning
confidence: 99%
“…One is Suppressor of Hairy wing [Su(Hw)], a twelve zinc finger protein encoded by the suppressor of Hairy wing [su(Hw)] gene, which binds to the repeated sequence motifs in the gypsy insulator (Dorsett, 1990;Spana and Corces, 1990). Of the protein domains comprising Su(Hw), 9 out of 12 zinc fingers and a domain of approximately 150 amino acids including the C-terminal leucine zipper, but not the N-and C-terminal acidic regions, are required for enhancer blocking (Harrison et al, 1993;Kim et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Su(Hw):706-944 was made by cloning the PvuII to HindIII 713-bp fragment of the su(Hw) cDNA into the EcoRV and HindIII sites of pING14.1. Mutant su(Hw) zinc finger domains described previously (21) were amplified by PCR with a 5Ј-primer with an NcoI site and an initiation codon, and a 3Ј-primer with an EcoRV site, and the resulting DNA fragments were cloned upstream of the HindIII (blunted) to SspI su(Hw) cDNA fragment with the termination codon into the NcoI and BamHI (blunted) sites of a pGEM3Z (Promega) vector modified to lack the polylinker HindIII site.…”
Section: Methodsmentioning
confidence: 99%
“…Of the protein domains comprising su(Hw), 9 out of 12 Zinc fingers and the C-terminal leucine zipper, but not the N-and Cterminal acidic regions, are required for enhancer blocking (Harrison et al 1993;Kim et al 1996). Molecular analysis of gypsy-induced mutations suggested that the retrotransposon had position-dependent enhancer-blocking activity.…”
Section: Proteins With Enhancer-blocking Abilitymentioning
confidence: 99%